Geochemical Studies on the Minerals Obtained by the Dry Valley Drilling Project - Watanuki, Kunihiko; Morikawa, Hideki (1975)
P(論文) Preliminary X-ray diffraction mineral analysis was carried out at the Thiel Earth Sciences Laboratory, McMurdo Station, on about three hundred samples from DVDP #6,from Lake Vida and from the McMurdo region. Chemical analyses of some of the minerals were carried out at our laboratory in Tokyo. From mineral species found in the core, it was suggested that there was some hydrothermal effect in the area. The secondary minerals of the Lake Vida core are different from those of the Ross Island core, and this indicates a differences in geological history between these sites. Using the distribution coefficient of alkaline earth elements in calcite, chemical constituents of the mineral-forming solution were calculated. The calcite might have been deposited from Sr- and Mg-poor solution compared to sea water. From the calculation using Debye-Huckel equation, the ground water at Lake Vanda is almost in equilibrium with calcium salfate but the lake water is supersaturated with calcium sulfate. departmental bulletin paper